A paleomagnetic and rock magnetic study of the Manicouagan impact structure: Implications for crater formation and geodynamo effects. Issue 2 (1st February 2016) - Eitel, Michael; Gilder, Stuart A.; Spray, John; Thompson, Lucy; Pohl, Jean
Abstract: We report rock magnetic and paleomagnetic data from the ~214 Ma Manicouagan (Canada) impact crater based on 25 widely distributed sites of impact melt and basement rocks collected at the surface as well as from boreholes drilled to depths ≤1.5 km. Titanomagnetite and titanohematite carry the magnetic remanence in impact melts above 320 m elevation and in most basement rocks. Impact melts below 320 m contain solely titanomagnetite. Magnetic susceptibility and saturation magnetization, proxies for titanomagnetite concentration, increase more than tenfold toward the base of the thickest impact melt that underwent fractional crystallization. The titanomagnetite‐enriched zone partially contributes to a 2000 nT magnetic anomaly in the crater's center. Stepwise demagnetization reveals a single, normal polarity magnetization component in all samples regardless of the magnetic phases present. Coeval lock‐in remanence times for titanomagnetite and titanohematite indicate that the titanohematite formed >570°C during oxi‐exsolution. The average paleomagnetic direction and intensity coincide well with 214 Ma reference values. We find no evidence for an aberration of the geomagnetic field over the several thousands of years it took to cool a 481 m thick portion of the impact melt body. Hence, the energy released by the Manicouagan impact that created one of the 10 largest known craters on Earth provoked no measurable disturbance of the geodynamo. Magnetic anisotropy of clast‐free impact melts define magnetic lineation directions that are, in places, radially oriented with respect to the crater's center. Centrifugal flow of the melt within the evolving transient crater probably generated the fabric. Key Points: One of the largest impacts on Earth provoked no disturbance of the geodynamo Magnetic anisotropy of impact melt indicates radial flow during crater formation Titanohematite in the impact melt formed via degassing and oxygen diffusion